MICROSTRUCTURE AND PROPERTIES OF THE CU/CNTS COMPOSITE MATERIAL - FU ShaoLi; LI ShengJuan; LIU Ping; CHEN XiaoHong; LIU XinKuan; LI Wei (Jixie qiangdu)
Based on the synthesis of well-distributed Cu/CNTs composite powder,Cu/CNTs composite material was prepared by spark plasma sintering（ SPS）,and the sintering temperature is 650℃,the sintering pressure is 35 Mpa,the holding time is 10 min. We studied the microstructure and properties of Cu/CNTs composite material for various content of Cu/CNTs powder. The results show that CNTs distributed uniformly along the grain boundary in copper matrix and the CNTs-Cu interface with a certain binding force is formed and the conductivity、hardness、tensile strength are 82. 8% IACS、96. 4 HV、417 MPa,and the hardness as well as tensile strength are maximum when the percent of Cu/CNTs powder is 20%.